2021
DOI: 10.1016/j.ecns.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Cardiac Life Support Simulation for Nurse Anesthetists and Student Nurse Anesthetists

Abstract: Background: Advanced Cardiac Life Support (ACLS) and emergency resuscitation is a critical role for anesthesia providers. The application of a clinical ACLS simulation to a patient under anesthesia is important to provide educational review and determine if the knowledge and skill of managing emergency events deteriorates over time. Method: A surgical ACLS simulation training session was completed to test ACLS knowledge retention and provider skill. High-fidelity simulation was used with a pre-test and post-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…Considera-se importante destacar a atualidade dos estudos identificados sobre esta temática e a preponderância da literatura nacional sobre a validação de cenários clínicos (9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , visto que, no Brasil, há uma tendência para a prática da construção e validação de cenários voltados ao ensino simulado em enfermagem e sua apresentação em artigos científicos (20)(21)(22)25) , diferenciando-se da pesquisa em simulação no contexto internacional, que executa a validação do cenário por especialistas durante o percurso metodológico, mas, geralmente, não considera a sua descrição detalhada nos estudos (33)(34)(35) .…”
Section: Discussionunclassified
“…Considera-se importante destacar a atualidade dos estudos identificados sobre esta temática e a preponderância da literatura nacional sobre a validação de cenários clínicos (9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , visto que, no Brasil, há uma tendência para a prática da construção e validação de cenários voltados ao ensino simulado em enfermagem e sua apresentação em artigos científicos (20)(21)(22)25) , diferenciando-se da pesquisa em simulação no contexto internacional, que executa a validação do cenário por especialistas durante o percurso metodológico, mas, geralmente, não considera a sua descrição detalhada nos estudos (33)(34)(35) .…”
Section: Discussionunclassified
“…Previous studies have shown that simulation positively affects nursing students' learning and competency acquisition for managing emergency situations, like ALS [19]. Furthermore, simulation based on ALS improves knowledge retention and skills in nursing students [20] and minimizes the time it takes to act during these situations [15]. However, there are no studies that explore the experience of nursing students in the application of ALS techniques, considering the stressful situation they must face while working as a team, in order to identify the factors involved in performing ALS techniques, which is the novel nature of this study.…”
Section: Introductionmentioning
confidence: 94%
“…Estratégias de capacitação profissional voltadas para instigar a reflexão sobre a prática e melhorar a qualidade da assistência de enfermagem têm sido tema de estudo de diversos autores [1][2] . Nesses estudos, a aprendizagem se revela como elemento-chave da prática clínica e interfere direta e indiretamente na qualidade do serviço.…”
Section: Introductionunclassified